Bilingual Education and Learning Achievements in Anglophone and Francophone Sub-Saharan Africa - Jean-Baptiste SANFO (Mitra Palupi, 2022)
Background: There is limited evidence on the potential benefits of bilingual medium of instruction (MOI) in sub-Saharan Africa. Purpose: This study examines the association between bilingual MOI and learning outcomes in Senegal and Zambia, analyzes how the association varies among students from different linguistic backgrounds, and estimates how consistent the relational patterns are between the two countries. Design and methods: The study Employs hierarchical linear modelling with PISA for Development 2018 data. Results: Results show that bilingual MOI is negatively associated with reading but not mathematics and science in Senegal, but it is not associated with any of these learning achievement measures in Zambia. However, the association may be positive or negative across student linguistic backgrounds in both countries. Moreover, the relational patterns between the countries may be consistent or inconsistent depending on the measure of learning achievements or whether we consider a direct or indirect relation. Implications of the findings were discussed.